Ephemeroptera asociados a ocho afluentes de la Sierra Nevada de Santa Marta, Colombia (2016)
The Ephemeroptera are an order of insects very important in the benthic community, being bio-indicators of water quality, considering key conservation. Despite the dense hydrographic network of the Sierra Nevada de Santa Marta (SNSM), Colombia Caribbean region, knowledge of aquatic macroinvertebrates assemblage is insufficient; limnological studies have focused mostly on the Gaira River. The aim of this study was to determine the composition and structure of the order Ephemeroptera in eight basins of the SNSM. The samples were collected between October-November 2013. In situ physical and chemical parameters were measured; nutrients and microorganisms were analyzed in the laboratory. In addition, the taxonomic composition and abundance was determined; Likewise canonical correspondence analysis (CCA) with the physico-chemical and microbiological biological parameters was performed. 1924 individuals distributed in five families and 12 genera were collected. The most abundant taxa were Leptohyphes (25 %), Baetodes (25 %), and Prebaetodes (9 %). According to the CCA, the temperature was the variable that best explained the variance of the presence of taxa. The basins of the SNSM remain important reservoirs of diversity of aquatic organisms. The results are a contribution to the knowledge of the order Ephemeroptera.